2012
DOI: 10.1051/0004-6361/201117128
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of OCNformation from the HNCO + NH3solid-state thermal reaction

Abstract: Context. Solid-state features in infrared astronomical spectra can provide useful information on interstellar ices within different astrophysical environments. Solid OCN − has an absorption feature at 4.62 μm, which is observed in star formation regions only with a large source-to-source abundance variation. Aims. We aim to investigate the thermal formation mechanism of solid OCN − from HNCO on the basis of kinetic arguments. Methods. We experimentally studied the kinetics of the low-temperature OCN − formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…If the dominant formation route of HNCO (NH + CO) were efficient (Garrod et al 2008), destruction routes would be required to explain this. As mentioned above, the formation of OCN − by reaction of HNCO with H 2 O and NH 3 are favourable routes, the reactions having activation barriers of 26 ± 2 kJ mol −1 (3130 ± 240 K; Theule et al 2011) and 0.4 ± 0.1 kJ mol −1 (48 ± 12 K; Mispelaer et al 2012), respectively. Irradiation of HNCO with vacuum ultraviolet (VUV) radiation has been shown to produce formaldehyde (H 2 CO), formamide (NH 2 CHO), and urea (H 2 NCONH 2 ) (Raunier et al 2004).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…If the dominant formation route of HNCO (NH + CO) were efficient (Garrod et al 2008), destruction routes would be required to explain this. As mentioned above, the formation of OCN − by reaction of HNCO with H 2 O and NH 3 are favourable routes, the reactions having activation barriers of 26 ± 2 kJ mol −1 (3130 ± 240 K; Theule et al 2011) and 0.4 ± 0.1 kJ mol −1 (48 ± 12 K; Mispelaer et al 2012), respectively. Irradiation of HNCO with vacuum ultraviolet (VUV) radiation has been shown to produce formaldehyde (H 2 CO), formamide (NH 2 CHO), and urea (H 2 NCONH 2 ) (Raunier et al 2004).…”
Section: Introductionmentioning
confidence: 91%
“…Jones et al (2011) contend that the hydrogenation of HNCO is insignificant as a route to formamide formation because of the low barrier to the reaction HNCO + NH 3 (Raunier et al 2003a;Mispelaer et al 2012). While it is true that NH 3 does react rapidly with HNCO, the flux of hydrogen atoms onto a grain will be superior to the quantity of NH 3 molecules in the ice mantle.…”
Section: Astrophysical Implicationsmentioning
confidence: 99%
“…On reason would be that there is a distribution of diffusion coefficients (corresponding to a distribution of sizes of cracks and pores) and not a single diffusion coefficient. Convoluting the diffusion coefficient with a distribution of pores on the basis of Mispelaer et al (2012) improves the adequacy between the theoretical and experimental curve, but will add one more parameter to fit, the shape factor of the distribution. But this does not necessarily give more physical insight into the diffusion problem.…”
Section: Analysis Using Fick's Second Law Of Diffusionmentioning
confidence: 99%
“…Theule et al 2011 found an activation energy barrier for reaction (7) of 3127 K, which is too high to make this reaction important for the conditions and timescales typical for young stellar objects. In a follow-up study, Mispelaer et al 2012 determined a barrier of 48 K for reaction (6), indicating the latter pathway as the most promising one to form OCNand NH4 + . As stated before, OCNhas been observed, and NH4 + may have been identified in the solid state, but the focus here is to simulate dense molecular cloud conditions, well before thermal and energetic processing of ices become important.…”
Section: N + H → Nhmentioning
confidence: 99%